TINGKAT PARTISIPASI MASYARAKAT DALAM PENGEMBANGAN EKOWISATA KERUJUK BERBASIS MASYARAKAT DI DESA MENGGALA KECAMATAN PEMENANG KABUPATEN LOMBOK UTARA - Amalia Khairunnisa; Lalu Wirasapta Karyadi; Rosiady Husaenie Sayuti (JURNAL AGRIMANSION, 2021)
This study aims to: (1) analyze the level of community participation in the development of ecotourism referrals; (2) analyze what factors are related to the level of community participation in the development of referred ecotourism; (3) analyze what strategies can be applied to increase community participation in the development of ecotourism referrals. The research method used in this research is descriptive method. The research was conducted in Kerujuk Hamlet, Mengala Village which was selected by purposive sampling with the consideration that the hamlet has an ecotourism program that involves the community. The determination of the number of respondents was determined by proportionate stratified random sampling using the Slovin formula and the number of respondents was determined to be 43 respondents. The collected data was then analyzed using a scoring system, Spearman rank correlation test analysis and SWOT analysis. The results showed that the level of community participation was included in the low category because community involvement was still lacking in all stages of activities carried out in an effort to develop ecotourism referrals. Factors related to the level of community participation are non-formal education (skills), income, length of stay and age. The strategy that can be applied in an effort to increase community participation is the WO strategy or weakness-opportunity, where cooperative efforts with the government or educational institutions are carried out to improve the quality of human resources to be more independent in managing creative and innovative referral ecotourism.